APUSPO (Automatic Air Purifier Smart Pot) Pemanfaatan Lidah Mertua dalam Monitoring Udara dengan Penambahan Konsep Self Watering - Syauqiyah Marwah Sahara Achmad; Aulia Luthfi Tri Malika; Indrato Dwi Atmoko; Susanti Rahayu (Jurnal Integrasi Sains dan Quran, 2024)
Indoor air pollution, especially at home, is very dangerous for human health, because in general humans spend more time doing activities at home. Tongue-in-law plants are ornamental plants that can absorb pollutants in the air, can produce oxygen and can absorb toxic gases. This study aims to design an air quality monitoring tool by utilizing the tongue-in-law plant as an air pollution filter and adding the Self Watering Concept. This research uses a descriptive method approach. Data collection methods are carried out by observation, experimentation, and literature study. Testing parameters include testing the suitability of the tool in monitoring air in the room, testing the effectiveness of the tool in cleaning pollution in the room. Based on the test results, it is found that the working system on the tool is in accordance with the air pollution standard index (ISPU) parameters in monitoring the air in the room and this air purification system can more quickly absorb pollution in a large room. APUSPO successfully monitors air pollution levels in the room using LCD and indicator lights.